(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
This endoparasitic eulophid is originally widespread in Australia and attacks the well-known gall-inducer wasp of eucalyptus, Ophelimus maskelli (Ashmead); recently, it has been deliberately released for biological control of the latter into different Mediterranean countries: Israel (6 sites), Campania (southern continental Italy) and Sicily (western side). In summer 2007, author detected a diffuse presence of C. chamaeleon in Basilicata andApulia (southern Italy); he obtained a few adults in June, from flowering branches of Eucalyptus camaldulensis Dehnh., and several adults more in July-August from samples of300 eucalyptus leaves. Likely, the positive localities shelter the offspring of the C. chamaeleon strains previously released in Campania and/or western Sicily. In any case, the abundance of this parasitoid in Basilicata and Apulia does confirm it to be hugely quick in colonising new territories around the introduction sites, as already reported in the literature.